Comparative Effects of Metamizole (Dipyrone) and Naproxen on Renal Function and Prostacyclin Synthesis in Salt-Depleted Healthy Subjects - A Randomized Controlled Parallel Group Study - Blaser, Lea S; Duthaler, Urs; Bouitbir, Jamal; Leuppi-Taegtmeyer, Anne B; Liakoni, Evangelia; Dolf, Reto; Mayr, Michael; Drewe, Jürgen; Krähenbühl, Stephan; Haschke, Manuel (Frontiers in Pharmacology, 2021)
Aims. The objective was to investigate the effect of metamizole on renal function in healthy, salt-depleted volunteers. In addition, the pharmacokinetics of the four major metamizole metabolites were assessed and correlated with the pharmacodynamic effect using urinary excretion of the prostacyclin metabolite 6-keto-prostaglandin F1α. Methods. Fifteen healthy male volunteers were studied in an open-label randomized controlled parallel group study. Eight subjects received oral metamizole 1000 mg three times daily and seven subjects naproxen 500 mg twice daily for 7 days. All subjects were on a low sodium diet (50 mmol sodium/day) starting one week prior to dosing until the end of the study. Glomerular filtration rate was measured using inulin clearance. Urinary excretion of sodium, potassium, creatinine, 6-keto-prostaglandin F1α, and pharmacokinetic parameters of naproxen and metamizole metabolites were assessed after the first and after repeated dosing. Results. In moderately sodium-depleted healthy subjects, single or multiple dose metamizole or naproxen did not significantly affect inulin and creatinine clearance or sodium excretion. Both drugs reduced renal 6-keto-prostaglandin F1α excretion after single and repeated dosing. The effect started 2 hours after intake, persisted for the entire dosing period and correlated with the concentration-profile of naproxen and the active metamizole metabolite 4-methylaminoantipyrine (4-MAA). PKPD modelling indicated less potent COX-inhibition by 4-MAA (EC50 0.69 ± 0.27µM) compared with naproxen (EC50 0.034 ± 0.033 µM). Conclusions. Short term treatment with metamizole or naproxen has no significant effect on renal function in moderately sodium depleted healthy subjects. At clinically relevant doses, 4-MAA and naproxen both inhibit COX-mediated renal prostacyclin synthesis.